In depression, bacterial translocation may drive inflammatory responses, oxidative and nitrosative stress (O&NS), and autoimmune responses directed against O&NS‐damaged neoepitopes. (17th August 2012) - Maes, M.; Kubera, M.; Leunis, J.‐C.; Berk, M.; Geffard, M.; Bosmans, E.
<x xml:space="preserve">Abstract</x> Maes M, Kubera M, Leunis J‐C, Berk M, Geffard M, Bosmans E. In depression, bacterial translocation may drive inflammatory responses, oxidative and nitrosative stress (O&NS), and autoimmune responses directed against O&NS‐damaged neoepitopes. Objective: Depression is accompanied by activation of immuno‐inflammatory and oxidative and nitrosative stress (IO&NS) pathways, and increased IgM/IgA responses to lipopolysaccharide (LPS) of gram‐negative commensal bacteria. The latter suggests that bacterial translocation has caused IgM/IgA responses directed against LPS. Bacterial translocation may drive IO&NS responses. Method: To examine the associations between IgM/IgA responses to LPS and IO&NS measurements, including plasma/serum interleukin‐1 (IL‐1), tumor necrosis factor (TNF)α, neopterin, lysozyme, oxidized LDL (oxLDL) antibodies, peroxides, and IgM (auto)immune responses against malondialdehyde (MDA), azelaic acid, phophatidyl inositol (Pi), NO‐tryptophan and NO‐tyrosine in depressed patients and controls. Results: We found significant positive associations between IgM/IgA responses to LPS and oxLDL antibodies, IgM responses against MDA, azelaic acid, Pi, NO‐tryptophan, and NO‐tyrosine. The IgA responses to LPS were correlated with lysozyme. There were no significant positive correlations between the IgM/IgA responses to LPS and IL‐1 and neopterin. Conclusion: The findings show that in depression there is an association between increased bacterial translocation and lysozyme production, an antibacterial compound, O&NS processes, and autoimmune responses directed against O&NS generated neoantigenic determinants. It is suggested that bacterial translocation may drive IO&NS pathways in depression and thus play a role in its pathophysiology.